Rural Poverty Reduction and Economic Transformation in China : A Decomposition Approach - Lugo, Maria Ana; Niu, Chiyu; Yemtsov, Ruslan (World Bank, Washington, DC, 2021)
Rural poverty in China fell from 96 percent in 1980 to less than 1 percent of the population in 2019. Using PovcalNet data for China and a set of comparable countries, this paper estimates growth-poverty elasticities. It finds that China stands out for its record of sustained, fast growth, rather than because of an unusually high growth-poverty elasticity. In addition, changes in mean consumption, rather than changes in the distribution, drive poverty reduction. Furthermore, until 2010, changes in inequality attenuated the impact of growth on poverty. The paper also studies which channels mattered the most for rural poverty reduction by applying a decomposition framework to multiple rounds of Chinese Household Income Project surveys conducted in 1988, 1995, 2002, 2007, 2013, and 2018. The findings show that broad-based, labor-intensive growth in agriculture was initially the main driving force for rural poverty reduction, followed by the expansion of non-agriculture sectors. As the country’s poverty rate approached 10 percent by 2007, transfers from migrant workers and, later, public transfers became the major drivers of further rural poverty reduction. Throughout the period, the fall in the demographic dependency rate also played a significant role. As China’s living standards continue to rise, the official definition of poverty will have to adjust to the higher minimum. Continued structural transformation and the inclusive growth agenda retain crucial importance for sustained poverty reduction.